2019
DOI: 10.1186/s41687-019-0136-z
|View full text |Cite
|
Sign up to set email alerts
|

Patient reported outcomes can improve performance status assessment: a pilot study

Abstract: Background Patient performance status is routinely used in oncology to estimate physical functioning, an important factor in clinical treatment decisions and eligibility for clinical trials. However, validity and reliability data for ratings of performance status have not been optimal. This study recruited oncology patients who were about to begin emetogenic palliative or adjuvant chemotherapy for treatment of solid tumors. We employed actigraphy as the gold standard for physical activity level. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…Five studies calculated concordance statistics for both KPS and ECOG. Two studies (Conill et al 21 and de Borja et al 25) reported higher inter-rater agreement for KPS, and three studies (Taylor et al 22; Schnadig et al 27; Collins et al 34) reported similarly for ECOG.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Five studies calculated concordance statistics for both KPS and ECOG. Two studies (Conill et al 21 and de Borja et al 25) reported higher inter-rater agreement for KPS, and three studies (Taylor et al 22; Schnadig et al 27; Collins et al 34) reported similarly for ECOG.…”
Section: Resultsmentioning
confidence: 98%
“…Thirty-two articles were identified for inclusion in level 2 screening, after which 16 articles underwent data extraction. Ultimately, 14 articles21–34 were included in our review (figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Convincing studies were performed by Basch et al [ 8 ] and Denis et al [ 9 ], which suggest that regular contact between patient and HCP via eHealth tools also improves overall survival. Furthermore, Broderick et al [ 10 ] reported that the performance status assessment can be improved before initiation of oncologic treatment by PRO. In the literature review by Anatchkova et al [ 11 ] regarding PRO use, it became apparent that PRO is still not commonly used in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…2,22,45,46,48 Further, emerging data from HICs suggest PROs offer superior assessment of performance status when compared to traditional physician-reported measures. 49 We observed significantly increased mortality risk and worse survival in our cohort among patients with physician-reported LPS [?] 70 and patient-reported Pain Intensity of 10 at diagnosis.…”
Section: Discussionmentioning
confidence: 99%